The South China Sea a crucible of regional cooperation or conflict-making sovereignty claims? - Jenner, C. J. (Christopher John).; Tran, Truong Thuy (New York Cambridge University Press, 2016)
"As a primary trade route for more than half of the world's shipping, the location of potentially huge oil and gas reserves, and the main source of protein in maritime South- East Asia, the South China Sea is a governing determinant of security, prosperity and development in East Asia and the wider Indo-Pacific region. The disputes in the South China Sea have long been seen as a source of tension and instability in the region. Although peace has been maintained until now, the South China Sea is the epicentre of changes in the international balance of power which have the potential to trigger military conflict. The South China Sea sovereignty disputes are among the most complicated in the world and engage claims from Brunei, China, Malaysia, Philippines, Taiwan, and Vietnam. Given the complex convergence of national interests in the region, the prospect of settling the decades-old disputes completely is very slim"--Provided by publisher.
Keywords: Territorial waters -- South China Sea Region; Arbitration (International law); Jurisdiction (International law); Maritime boundaries; South China Sea -- International status; South China Sea Region -- Politics and government